Lie Ideals with Multiplicative Homomultipliers on Near-Rings - Farhan, Enaam (Iraqi Journal of Science, 2024)
In this study, the new types of mappings on the rings and near-rings are defined, which are named multiplicative homoleft multipliers, multiplicative homoright multipliers and multiplicative homo multipliers. We also present examples that show the existence of such mappings. Moreover, we study how these mappings effected on the construction of near-rings.